Tearing down walls: opening the border between hospital and ambulatory care for quality improvement in Germany - Szecsenyi, Joachim; Wensing, Michel (International journal for quality in health care, 2012)
Abstract. The hospital benchmarking system in Germany was originally introduced to detect unintended consequences of reimbursement based on diagnosis-related